Aramid lithium battery separator with low closed pores and high film breakage and preparation method thereof
By adopting aramid lithium battery separator with low closed pore and high rupture, the porous layer structure of heat-resistant polymer and low melting point polymer is used to solve the problem of insufficient heat resistance of the existing separator at high temperatures, achieving higher rupture temperatures and lower closed pore temperatures, significantly improving the safety performance and energy density of the battery.
Patent Information
- Application Number
- CN202210528969.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-05-16
AI Technical Summary
The existing lithium battery separators are insufficient in heat resistance at high temperatures, which cannot effectively prevent battery short circuits, and the closed-hole temperature is high, affecting battery safety performance.
A low-closed pore and high-breaking film is used for aramid lithium battery separator. The preparation method includes preparing a polymeric liquid of heat-resistant polymer and a low-melting point polymer, mixing and adding a pore-forming agent, forming a film through phase conversion method to form a porous layer separator.
The heat resistance and rupture temperature of the diaphragm are significantly improved, and the closed-cell temperature is reduced, thereby enhancing the safety performance of the battery and improving the energy density and range of the battery.
Smart Images

Figure BDA0003645775820000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium battery materials, and in particular relates to an aramid lithium battery separator with low closed pores and high film rupture rate and a preparation method thereof. Background Art
[0002] With the unexpected growth of new energy vehicles, the demand for power lithium battery separators continues to grow. People are paying more and more attention to the range and safety of power batteries. The separator can block the contact between the positive and negative electrodes. At present, power lithium battery separators mostly use polyolefin separators. In order to improve the range and heat resistance, polyvinylidene fluoride (PVDF) or ceramic modification is usually performed on the polyolefin separator. PVDF coating is used to improve the bonding performance between the separator and the electrode, and ceramic coating is used to improve the wettability and heat resistance of the separator and the electrolyte. However, since the base film of these two methods is polyolefin, they can only improve the heat resistance of the separator to a certain extent, and cannot increase the membrane rupture temperature of the separator to above 200°C.
[0003] When an exothermic reaction occurs inside the battery, such as self-heating, overcharging, or external short circuit, a large amount of heat will be generated. At this time, if the diaphragm forms closed micropores, then the continuous transmission of ions is blocked to form a short circuit, which can protect the battery. The temperature when the micropores are closed is the closed-pore temperature. For lithium batteries, it is better to have a lower closed-pore temperature. When the temperature rises, the micropores can be closed to prevent short circuits, thereby improving the safety of battery use. Summary of the invention
[0004] The purpose of the present invention is to provide an aramid lithium battery separator with low closed pores and high rupture temperature and a preparation method thereof, so as to overcome the defects of the prior art. The present invention can simultaneously significantly increase the separator rupture temperature and reduce the closed pore temperature, thereby doubly improving the battery safety performance.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A method for preparing an aramid lithium battery separator with low closed pores and high membrane rupture, comprising the following steps:
[0007] (1) preparing a polymerization solution of a heat-resistant high polymer with a concentration of 1.0 wt / % to 20 wt / %, and preparing a polymerization solution of a low-melting-point polymer with a concentration of 0.5 wt / % to 30 wt%;
[0008] (2) mixing a polymer solution of a low melting point polymer and a polymer solution of a heat-resistant high polymer in a volume ratio of 1:1 to obtain a mixed solution, adding a pore-forming agent to the mixed solution, and stirring the mixed solution to obtain a casting solution;
[0009] (3) The casting liquid is coated on the substrate, firstly passed through a steam bath, then immersed in water for phase inversion film formation, and then dried and cooled to form a heat-resistant polymer porous layer, wherein the heat-resistant polymer porous layer is an aramid lithium battery separator with low closed pores and high membrane rupture.
[0010] Furthermore, the heat-resistant high polymer is any one of meta-aramid, para-aramid and aramid 1314.
[0011] Furthermore, when the heat-resistant high polymer is meta-aramid, the preparation process of the polymer solution of the heat-resistant high polymer is as follows: adding a cosolvent to an organic solvent A under nitrogen protection to dissolve meta-phenylenediamine, reacting in an ice-water bath, adding isophthaloyl chloride while stirring, and adding a neutralizer to neutralize after a preset reaction time to obtain a meta-aramid polymer solution with a concentration of 1wt / %-20wt / %;
[0012] When the heat-resistant high polymer is para-aramid, the preparation process of the polymer solution of the heat-resistant high polymer is as follows: adding a cosolvent to an organic solvent A under nitrogen protection to dissolve p-phenylenediamine, reacting in an ice-water bath, adding terephthaloyl chloride while stirring, and adding a neutralizer to neutralize after a preset reaction time to obtain a para-aramid polymer solution with a concentration of 1wt / %-20wt / %;
[0013] When the heat-resistant high polymer is aramid 1314, the preparation process of the polymer solution of the heat-resistant high polymer is as follows: under nitrogen protection, a cosolvent is added to an organic solvent A to dissolve a mixture of p-phenylenediamine and m-phenylenediamine, wherein the mass ratio of p-phenylenediamine to m-phenylenediamine is (1-9): (9-1); the reaction is carried out in an ice-water bath; while stirring, a mixture of terephthaloyl chloride and isophthaloyl chloride is added, wherein the mass ratio of terephthaloyl chloride to isophthaloyl chloride is (1-9): (9-1); after a preset reaction time, a neutralizer is added for neutralization to obtain an aramid 1314 polymer solution with a concentration of 1wt / %-20wt / %.
[0014] Furthermore, the organic solvent A is any one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone; the co-solvent is lithium chloride or calcium chloride; and the neutralizer is any one of sodium hydroxide, calcium hydroxide and potassium hydroxide.
[0015] Furthermore, the low melting point polymer is any one or more combinations of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, ethylene-octene copolymer, ethylene-propylene copolymer, nylon 6 / 66 / 12 terpolymer, nylon 6 / 66 / 1010 terpolymer, nylon 6 / 66 / 610 terpolymer and polyethylene succinate.
[0016] Furthermore, the preparation process of the polymer solution of the low melting point polymer is as follows: dissolving the low melting point polymer in an organic solvent B to obtain the polymer solution of the low melting point polymer;
[0017] The organic solvent B is any one or more combinations of tetrahydrofuran, acetone, dimethyl sulfoxide and tetramethyl urea.
[0018] Furthermore, the melting point of the low-melting-point polymer is 100-130°C.
[0019] Furthermore, the pore-forming agent is any one or more combinations of calcium chloride, lithium chloride, polypyrrolidone and polyethylene glycol, and the amount of the pore-forming agent added is 2wt / %-10wt% of the mass of the mixed solution.
[0020] Furthermore, the temperature of the steam bath is 30-60° C., and the humidity is 50%-100%.
[0021] A low-closed-pore and high-breakage-rate aramid lithium battery separator, wherein the low-closed-pore and high-breakage-rate aramid lithium battery separator has a thickness of 5-30 μm and a pore size of 0.5-3 μm.
[0022] Compared with the prior art, the present invention has the following beneficial technical effects:
[0023] The present invention adopts a heat-resistant polymer as a porous base layer, which can remove the limitation of the polyolefin diaphragm on the heat resistance. There is no thermal shrinkage at a temperature of 250°C, which can greatly improve the heat resistance of the diaphragm. In addition, by adding a low-melting point polymer, the diaphragm has a low closed-cell temperature, providing double protection for the safety performance of the lithium battery. At the same time, the heat-resistant polymer as a porous base layer can increase the porosity of the diaphragm, improve the wettability of the electrolyte, increase the battery energy density, and increase the cruising range of the vehicle.
[0024] Furthermore, the present invention can improve the thermal stability of the diaphragm. Using a high temperature resistant polymer as the porous base layer can greatly improve the heat resistance of the diaphragm and reduce the shrinkage value of the diaphragm at high temperatures. The thermal shrinkage value at 250°C for 1h is 0.
[0025] Furthermore, during the first charge and discharge process of a lithium battery, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material, referred to as the SEI film, which can prevent the interaction between the electrolyte and the graphite negative electrode. However, when the temperature rises above 100°C, the SEI film will undergo a decomposition reaction, causing an irreversible reaction between the electrolyte and the negative electrode surface, resulting in the formation of irreversible capacity and the generation of heat, causing the temperature to rise further. When the temperature exceeds 130°C, the SEI film will completely disintegrate, and side reactions will occur when the electrode and the electrolyte come into contact. When enough heat is accumulated, the electrolyte decomposes and eventually thermally runs away. Therefore, the present invention selects a temperature in the range of 100-130°C, and the membrane becomes closed to avoid contact between the positive and negative electrodes of the battery, and the membrane rupture temperature can be greatly increased by selecting aramid 1313, aramid 1414, and aramid 1314 as the diaphragm, thereby improving the battery safety from both the closed-pore temperature and the membrane rupture temperature.
[0026] Furthermore, the present invention can reduce the thermal closure temperature of the diaphragm. The selected low-melting polymer has a melting point of 100-130°C. The diaphragm can undergo closure behavior before the temperature reaches the point where the SEI film is completely decomposed, thereby preventing the temperature from rising rapidly and improving battery safety.
[0027] Furthermore, the present invention can improve the uniformity of the micropores of the diaphragm. Before the casting liquid enters the water tank to form the film, a steam bath is added to pre-form the holes, thereby preventing the casting liquid from solidifying quickly after entering the water tank, affecting the uniformity of the holes inside the diaphragm and the size of the surface pores, and improving the air permeability of the diaphragm.
[0028] Furthermore, the present invention can improve the cycle performance of the battery. The heat-resistant polymer is used as the base layer through phase conversion wet film formation. The pore size of the diaphragm is relatively large. Adding a low-melting point polymer to the casting liquid can improve the pore size of the diaphragm, thereby reducing the self-discharge of the battery, reducing the attenuation of the battery during the cycle process, and improving the cycle performance of the battery. DETAILED DESCRIPTION
[0029] The present invention is further described below.
[0030] A lithium battery separator with low closed pores and high rupture rate, the separator is mainly composed of a heat-resistant polymer porous layer, the heat-resistant polymer porous layer is prepared by a casting liquid composed of a heat-resistant polymer and a low-melting point polymer through a phase conversion method, the low-melting point polymer is uniformly dispersed in the heat-resistant polymer, the heat-resistant polymer porous layer has a thickness of 5-30μm and a pore size of 0.5-3μm.
[0031] The heat-resistant polymer is any one of meta-aramid, para-aramid and aramid 1314; the low-melting-point polymer is any one of polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, ethylene-octene copolymer, ethylene-propylene copolymer, nylon 6 / 66 / 12 terpolymer, nylon 6 / 66 / 1010 terpolymer, nylon 6 / 66 / 610 terpolymer and polyethylene succinate; the melting point of the low-melting-point polymer is 100-130°C;
[0032] A method for preparing a lithium battery separator with low closed pores and high film rupture, comprising the following steps:
[0033] (1) preparing a polymerization solution of a heat-resistant high polymer with a concentration of 1-20 wt / %, and preparing a polymerization solution of a low-melting-point polymer with a concentration of 0.5-30 wt / %;
[0034] (2) mixing a polymer solution of a low melting point polymer and a polymer solution of a heat-resistant high polymer in a volume ratio of 1:1 to obtain a mixed solution, adding a pore-forming agent to the mixed solution, wherein the amount of the pore-forming agent added is 2wt / %-10wt% of the mass of the mixed solution, and stirring to obtain a casting solution;
[0035] (3) The casting liquid is coated on a release film or a stainless steel belt through a coating device, and the coating method is any one of micro-concave roller coating, doctor blade coating, slit extrusion, and wire rod coating. It first passes through a steam bath (the temperature of the steam bath is 30-60°C, and the humidity is 50%-100%), and then is immersed in a water tank for phase inversion film formation. After entering a drying oven for drying, it is cooled and shaped, and then rolled up to obtain a heat-resistant polymer porous layer, which is an aramid lithium battery separator with low closed pores and high film rupture.
[0036] The preparation of the polymer solution of the heat-resistant high polymer is specifically as follows:
[0037] When the heat-resistant high polymer is meta-aramid, the preparation process of the polymer solution of the heat-resistant high polymer is as follows: adding a cosolvent to an organic solvent A under nitrogen protection to dissolve meta-phenylenediamine, reacting in an ice-water bath, adding isophthaloyl chloride while stirring, and adding a neutralizer to neutralize after a preset reaction time to obtain a meta-aramid polymer solution;
[0038] When the heat-resistant high polymer is para-aramid, the preparation process of the polymer solution of the heat-resistant high polymer is as follows: adding a cosolvent to an organic solvent A under nitrogen protection to dissolve p-phenylenediamine, reacting in an ice-water bath, adding terephthaloyl chloride while stirring, and adding a neutralizer to neutralize after a preset reaction time to obtain a para-aramid polymer solution;
[0039] When the heat-resistant high polymer is aramid 1314, the preparation process of the polymer solution of the heat-resistant high polymer is as follows: adding a cosolvent to an organic solvent A under nitrogen protection to dissolve a mixture of p-phenylenediamine and m-phenylenediamine, wherein the mass ratio of p-phenylenediamine to m-phenylenediamine is (1-9): (9-1), reacting in an ice-water bath, adding a mixture of terephthaloyl chloride and isophthaloyl chloride while stirring, wherein the mass ratio of terephthaloyl chloride to isophthaloyl chloride is (1-9): (9-1), and adding a neutralizer to neutralize after a preset reaction time to obtain an aramid 1314 polymer solution;
[0040] The preparation of the polymerization liquid of the low melting point polymer is specifically as follows: dissolving the low melting point polymer in an organic solvent B to obtain the polymerization liquid of the low melting point polymer.
[0041] The organic solvent A is any one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone; the cosolvent is any one of lithium chloride and calcium chloride; the neutralizer is any one of sodium hydroxide, calcium hydroxide, and potassium hydroxide; the organic solvent B is any one or more of tetrahydrofuran, acetone, dimethyl sulfoxide, and tetramethyl urea; the pore former is any one or more of calcium chloride, lithium chloride, polypyrrolidone, and polyethylene glycol, and the amount of the pore former added is 2wt / %-10wt% of the mass of the mixed solution.
[0042] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.
[0043] The following detailed description is the description of the embodiments, and is intended to provide further detailed description of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used in the present invention are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present invention.
[0044] Example 1
[0045] Preparation of meta-aramid polymer solution: Under nitrogen protection, LiCl was added to 250 ml of DMAc (N,N-dimethylacetamide), 1.0814 g of m-phenylenediamine was dissolved, and the reaction was carried out in an ice-water bath. 2.0302 g of isophthaloyl chloride was slowly added while stirring. After reacting for 30 minutes, 0.074 g of calcium hydroxide was added for neutralization to obtain a meta-aramid polymer solution with a concentration of 1.0 wt / %.
[0046] Preparation of casting solution: dissolving polyvinylidene fluoride-hexafluoropropylene in 250 ml tetrahydrofuran at a mass fraction of 0.5 wt%, mixing with the above meta-aramid polymer solution to obtain a mixed solution, adding 2 wt % of the mass of the mixed solution as a pore-forming agent calcium chloride, stirring evenly to obtain a casting solution;
[0047] Preparation of heat-resistant polymer porous layer: The above casting solution is coated on a stainless steel belt through a coating device, first passed through a steam bath with a temperature of 30°C and a humidity of 50%, then immersed in a water tank for phase inversion film formation, dried in a drying oven, cooled and shaped, and rolled up to a thickness of 5 μm.
[0048] Example 2
[0049] Preparation of para-aramid polymer solution: Under nitrogen protection, CaCl2 was added to 250 ml of NMP (N-methylpyrrolidone) to dissolve 21.628 g of p-phenylenediamine. The reaction was carried out in an ice-water bath. 40.604 g of terephthaloyl chloride was slowly added while stirring. After reacting for 30 minutes, 1.48 g of calcium hydroxide was added for neutralization to obtain a para-aramid polymer solution with a concentration of 20 wt / %.
[0050] Preparation of casting solution: dissolving 30 wt% of ethylene-octene copolymer in 250 ml of tetrahydrofuran, mixing with the para-aramid polymer solution to obtain a mixed solution, adding 10 wt% of the mixed solution as a pore-forming agent, lithium chloride, and stirring to obtain a casting solution;
[0051] Preparation of heat-resistant polymer porous layer: The above casting solution is coated on a stainless steel belt through a coating device, first passed through a steam bath with a temperature of 60°C and a humidity of 100%, then immersed in a water tank for phase inversion film formation, dried in a drying oven, cooled and shaped, and rolled up to a thickness of 30 μm.
[0052] Example 3
[0053] Preparation of aramid 1314 polymer solution: Under nitrogen protection, CaCl2 was added to 250 ml of NMP (N-methylpyrrolidone), and 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine (mass ratio of 1:9) was dissolved. The reaction was carried out in an ice water bath, and 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride (mass ratio of 1:9) was slowly added while stirring. After reacting for 30 minutes, 0.74 g of calcium hydroxide was added for neutralization to obtain an aramid 1314 polymer solution with a concentration of 10 wt / %.
[0054] Preparation of casting solution: dissolving polyethylene glycol succinate in 250 ml of tetrahydrofuran at a mass fraction of 10 wt%, mixing with the above-mentioned aramid 1314 polymer solution to obtain a mixed solution, adding 5 wt % of the mass of the mixed solution as a pore-forming agent polyethylene glycol, and stirring evenly to obtain a casting solution;
[0055] Preparation of heat-resistant polymer porous layer: The above casting solution is coated on a stainless steel belt through a coating device, first passed through a steam bath with a temperature of 45°C and a humidity of 75%. Then it is immersed in a water tank for phase inversion film formation, then dried in a drying oven, cooled and shaped, and rolled up to a thickness of 15 μm.
[0056] Example 4
[0057] Preparation of aramid 1314 polymer solution: Under nitrogen protection, CaCl2 was added to 250 ml of DMF (N,N-dimethylformamide) to dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine (mass ratio of 1:1). The reaction was carried out in an ice water bath. While stirring, 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride (mass ratio of 1:1) was slowly added. After reacting for 30 minutes, 0.74 g of calcium hydroxide was added for neutralization to obtain an aramid 1314 polymer solution with a concentration of 10 wt / %.
[0058] Preparation of casting solution: dissolving nylon 6 / 66 / 12 terpolymer in 250 ml tetrahydrofuran at a mass fraction of 10 wt%, mixing with the above aramid 1314 polymer solution to obtain a mixed solution, adding 5 wt % of the mass of the mixed solution of pore former polypyrrolidone, and stirring to obtain a casting solution;
[0059] Preparation of heat-resistant polymer porous layer: The above casting solution is coated on a stainless steel belt through a coating device, first passed through a steam bath with a temperature of 45°C and a humidity of 75%. Then it is immersed in a water tank for phase inversion film formation, then dried in a drying oven, cooled and shaped, and rolled up to a thickness of 15 μm.
[0060] Example 5
[0061] Preparation of aramid 1314 polymer solution: Under nitrogen protection, CaCl2 was added to 250 ml of NMP (N-methylpyrrolidone) to dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine (mass ratio of 9:1). The reaction was carried out in an ice water bath. While stirring, 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride (mass ratio of 9:1) was slowly added. After reacting for 30 minutes, 0.74 g of calcium hydroxide was added for neutralization to obtain an aramid 1314 polymer with a concentration of 10 wt / %.
[0062] Preparation of casting solution: dissolving nylon 6 / 66 / 1010 terpolymer, nylon 6 / 66 / 610 terpolymer and polyvinylidene fluoride-trifluoroethylene (mass ratio 1:1:1) in 250 ml of tetrahydrofuran at a mass fraction of 10 wt%, mixing with the above-mentioned aramid 1314 polymer solution to obtain a mixed solution, adding 5 wt % of the mass of the mixed solution of pore-forming agents calcium chloride and lithium chloride (mass ratio of the two is 1:1), stirring evenly to obtain a casting solution;
[0063] Preparation of heat-resistant polymer porous layer: The above casting solution is coated on a stainless steel belt through a coating device, first passed through a steam bath with a temperature of 45°C and a humidity of 75%. Then it is immersed in a water tank for phase inversion film formation, then dried in a drying oven, cooled and shaped, and rolled up to a thickness of 15 μm.
[0064] Comparative Example 1:
[0065] A 7 μm PE-based film is commercially available.
[0066] Comparative Example 2:
[0067] Preparation of meta-aramid polymer solution: Under nitrogen protection, LiCl was added to 250 ml of DMAc (N,N-dimethylacetamide), 1.0814 g of m-phenylenediamine was dissolved, and the reaction was carried out in an ice-water bath. 2.0302 g of isophthaloyl chloride was slowly added while stirring. After reacting for 30 minutes, 0.074 g of calcium hydroxide was added for neutralization to obtain a meta-aramid polymer solution with a concentration of 1.0 wt / %.
[0068] Preparation of the casting solution: Add calcium chloride as a pore-forming agent to the meta-aramid polymer solution, the pore-forming agent calcium chloride accounts for 0.5wt% of the mass of the meta-aramid polymer solution, and stir evenly to obtain the casting solution.
[0069] Preparation of heat-resistant polymer porous layer: The above casting solution is coated on a stainless steel belt through a coating device, first passed through a steam bath with a temperature of 30°C and a humidity of 50%, then immersed in a water tank for phase inversion film formation, dried in a drying oven, cooled and shaped, and rolled up to a thickness of 5 μm.
[0070] Table 1 Performance of the diaphragm of the embodiment and the comparative example
[0071]
[0072] It can be seen from Table 1 that, compared with the PE-based film, the thermal closure temperature of the diaphragms prepared in Examples 1-5 with the addition of low-melting-point polymers is lower, and the film rupture temperature is increased to above 250°C; the PE film becomes transparent and shrinks at a temperature of 250°C; in Comparative Example 2, there is only a heat-resistant polymer porous layer, and no low-melting-point polymer is added. The diaphragm has no closure temperature, and the diaphragm will directly rupture after reaching a certain temperature.
[0073] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
Claims
1. A low closed-cell and high-breakdown aramid lithium battery separator, characterized in that: The aramid lithium battery separator with low closed pores and high membrane rupture is prepared by the following steps: Preparation of meta-aramid polymer solution: LiCl was added to 250 ml of N,N-dimethylacetamide under nitrogen protection, 1.0814 g of meta-phenylenediamine was dissolved, and the reaction was carried out in an ice-water bath. 2.0302 g of isophthaloyl chloride was slowly added while stirring. After reacting for 30 minutes, 0.074 g of calcium hydroxide was added for neutralization to obtain a meta-aramid polymer solution with a concentration of 1.0 wt / %; Preparation of casting solution: dissolve polyvinylidene fluoride-hexafluoropropylene in 250 ml tetrahydrofuran at a mass fraction of 0.5 wt%, mix with the above-mentioned meta-aramid polymer solution at a volume ratio of 1:1 to obtain a mixed solution, add 2 wt % of the mass of the mixed solution as a pore-forming agent calcium chloride, stir evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The above-mentioned casting liquid is coated on a stainless steel belt through a coating device, firstly passes through a steam bath, the temperature of the steam bath is 30°C, and the humidity is 50%, then immersed in a water tank for phase inversion film formation, then enters a drying oven for drying, cooling and shaping, and winding to obtain the aramid lithium battery separator with low closed pores and high film breakage; The thickness of the low-closed-pore and high-breakage-film aramid lithium battery separator is 5 μm, the thermal closed-pore temperature is 115° C., the breakage temperature is 265° C., and the battery capacity retention rate of the low-closed-pore and high-breakage-film aramid lithium battery separator after 100 cycles is 95.7%.
2. A method for preparing the aramid lithium battery separator with low closed pores and high rupture rate according to claim 1, characterized in that: The following steps are involved: Preparation of meta-aramid polymer solution: LiCl was added to 250 ml of N,N-dimethylacetamide under nitrogen protection, 1.0814 g of meta-phenylenediamine was dissolved, and the reaction was carried out in an ice-water bath. 2.0302 g of isophthaloyl chloride was slowly added while stirring. After reacting for 30 minutes, 0.074 g of calcium hydroxide was added for neutralization to obtain a meta-aramid polymer solution with a concentration of 1.0 wt / %; Preparation of casting solution: dissolve polyvinylidene fluoride-hexafluoropropylene in 250 ml tetrahydrofuran at a mass fraction of 0.5 wt%, mix with the above-mentioned meta-aramid polymer solution at a volume ratio of 1:1 to obtain a mixed solution, add 2 wt % of the mass of the mixed solution as a pore-forming agent calcium chloride, stir evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The above-mentioned casting liquid is coated on a stainless steel belt through a coating equipment, first passed through a steam bath with a temperature of 30°C and a humidity of 50%, then immersed in a water tank for phase inversion film formation, dried in a drying oven, cooled and shaped, and rolled up to obtain the low closed-pore and high rupture film aramid lithium battery separator.
3. A low closed-cell and high-breakdown aramid lithium battery separator, characterized in that: The aramid lithium battery separator with low closed pores and high membrane rupture is prepared by the following steps: Preparation of para-aramid polymer solution: Add CaCl2 to 250 ml of N-methylpyrrolidone under nitrogen protection, dissolve 21.628 g of p-phenylenediamine, react in an ice-water bath, slowly add 40.04 g of terephthaloyl chloride while stirring, and after reacting for 30 minutes, add 1.48 g of calcium hydroxide for neutralization to obtain a para-aramid polymer solution with a concentration of 20 wt / %; Preparation of casting solution: dissolving 30 wt% of ethylene-octene copolymer in 250 ml of tetrahydrofuran, and mixing with the above-mentioned para-aramid polymer solution at a volume ratio of 1:1 to obtain a mixed solution, adding 10 wt% of the mixed solution mass of pore-forming agent lithium chloride, and stirring to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The casting liquid is coated on a stainless steel belt through a coating device, firstly passed through a steam bath, the temperature of the steam bath is 60°C, the humidity is 100%, then immersed in a water tank for phase inversion film formation, then dried in a drying oven, cooled and shaped, to obtain the low closed-pore and high-breakage aramid lithium battery separator, and then rolled up to obtain the low closed-pore and high-breakage aramid lithium battery separator; The thickness of the low-closed-pore and high-breakage-film aramid lithium battery separator is 30 μm, the thermal closed-pore temperature is 120° C., the breakage temperature is 326° C., and the battery capacity retention rate of the low-closed-pore and high-breakage-film aramid lithium battery separator after 100 cycles is 98.2%.
4. A method for preparing the aramid lithium battery separator with low closed pores and high rupture rate according to claim 3, characterized in that: The following steps are involved: Preparation of para-aramid polymer solution: Add CaCl2 to 250 ml of N-methylpyrrolidone under nitrogen protection, dissolve 21.628 g of p-phenylenediamine, react in an ice-water bath, slowly add 40.04 g of terephthaloyl chloride while stirring, and after reacting for 30 minutes, add 1.48 g of calcium hydroxide for neutralization to obtain a para-aramid polymer solution with a concentration of 20 wt / %; Preparation of casting solution: dissolving 30 wt% of ethylene-octene copolymer in 250 ml of tetrahydrofuran, and mixing with the above-mentioned para-aramid polymer solution at a volume ratio of 1:1 to obtain a mixed solution, adding 10 wt% of the mixed solution mass of pore-forming agent lithium chloride, and stirring to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The above-mentioned casting liquid is coated on a stainless steel belt through a coating equipment, first passed through a steam bath, the temperature of the steam bath is 60°C, and the humidity is 100%, and then immersed in a water tank for phase inversion film formation, and then placed in a drying oven for drying and cooling to obtain the low closed-pore and high rupture film aramid lithium battery separator, which is then rolled up to obtain the low closed-pore and high rupture film aramid lithium battery separator.
5. A low closed-cell and high-breakdown aramid lithium battery separator, characterized in that: The aramid lithium battery separator with low closed pores and high membrane rupture is prepared by the following steps: Preparation of aramid 1314 polymer solution: Add CaCl2 to 250 ml of N-methylpyrrolidone under nitrogen protection, dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine in a mass ratio of 1:9, react in an ice water bath, slowly add 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride in a mass ratio of 1:9 while stirring, react for 30 minutes, add 0.74 g of calcium hydroxide for neutralization, and obtain an aramid 1314 polymer solution with a concentration of 10 wt / %; Preparation of casting solution: dissolve polyethylene glycol succinate in 250 ml of tetrahydrofuran at a mass fraction of 10 wt%, mix with the above aramid 1314 polymer solution at a volume ratio of 1:1 to obtain a mixed solution, add 5 wt % of the mass of the mixed solution as a pore-forming agent polyethylene glycol, stir evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The casting liquid is coated on a stainless steel belt through a coating device, firstly passed through a steam bath, the temperature of the steam bath is 45°C, the humidity is 75%, then immersed in a water tank for phase inversion film formation, then placed in a drying oven for drying and cooling to obtain the low closed-pore and high rupture aramid lithium battery separator, and then rolled up to obtain the low closed-pore and high rupture aramid lithium battery separator; The thickness of the low closed-pore and high rupture film aramid lithium battery separator is 15 μm, the thermal closed-pore temperature is 104° C., the rupture film temperature is 287° C., and the battery capacity retention rate of the low closed-pore and high rupture film aramid lithium battery separator after 100 cycles is 97.2%.
6. A method for preparing the aramid lithium battery separator with low closed pores and high rupture rate according to claim 5, characterized in that: The following steps are involved: Preparation of aramid 1314 polymer solution: Add CaCl2 to 250 ml of N-methylpyrrolidone under nitrogen protection, dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine in a mass ratio of 1:9, react in an ice water bath, slowly add 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride in a mass ratio of 1:9 while stirring, react for 30 minutes, add 0.74 g of calcium hydroxide for neutralization, and obtain an aramid 1314 polymer solution with a concentration of 10 wt / %; Preparation of casting solution: dissolving polyethylene glycol succinate in 250 ml of tetrahydrofuran at a mass fraction of 10 wt%, mixing with the above-mentioned aramid 1314 polymer solution to obtain a mixed solution, adding 5 wt % of the mass of the mixed solution as a pore-forming agent polyethylene glycol, and stirring evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The above-mentioned casting liquid is coated on a stainless steel belt through a coating equipment, first passed through a steam bath with a temperature of 45°C and a humidity of 75%, then immersed in a water tank for phase inversion film formation, and then placed in a drying oven for drying and cooling to obtain the aramid lithium battery separator with low closed pores and high rupture properties, which is then rolled up to obtain the aramid lithium battery separator with low closed pores and high rupture properties.
7. A low closed-cell and high-breakdown aramid lithium battery separator, characterized in that: The aramid lithium battery separator with low closed pores and high membrane rupture is prepared by the following steps: Preparation of aramid 1314 polymer solution: Add CaCl2 to 250 ml of N,N-dimethylformamide under nitrogen protection, dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine in a mass ratio of 1:1, react in an ice water bath, slowly add 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride in a mass ratio of 1:1 while stirring, react for 30 minutes, add 0.74 g of calcium hydroxide for neutralization, and obtain an aramid 1314 polymer solution with a concentration of 10 wt / %; Preparation of casting solution: dissolve nylon 6 / 66 / 12 terpolymer in 250 ml tetrahydrofuran at a mass fraction of 10 wt%, mix with the above aramid 1314 polymer solution at a volume ratio of 1:1 to obtain a mixed solution, add 5 wt % of the mass of the mixed solution of pore-forming agent polypyrrolidone, stir evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The casting liquid is coated on a stainless steel belt through a coating device, firstly passed through a steam bath, the temperature of the steam bath is 45°C, the humidity is 75%, then immersed in a water tank for phase inversion film formation, then placed in a drying oven for drying and cooling to obtain the low closed-pore and high rupture aramid lithium battery separator, and then rolled up to obtain the low closed-pore and high rupture aramid lithium battery separator; The thickness of the low-closed-pore and high-breakage-film aramid lithium battery separator is 15 μm, the thermal closed-pore temperature is 110° C., the breakage temperature is 305° C., and the battery capacity retention rate of the low-closed-pore and high-breakage-film aramid lithium battery separator after 100 cycles is 97.8%.
8. A method for preparing the aramid lithium battery separator with low closed pores and high rupture rate according to claim 7, characterized in that: The following steps are involved: Preparation of aramid 1314 polymer solution: Add CaCl2 to 250 ml of N,N-dimethylformamide under nitrogen protection, dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine in a mass ratio of 1:1, react in an ice water bath, slowly add 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride in a mass ratio of 1:1 while stirring, react for 30 minutes, add 0.74 g of calcium hydroxide for neutralization, and obtain an aramid 1314 polymer solution with a concentration of 10 wt / %; Preparation of casting solution: dissolving nylon 6 / 66 / 12 terpolymer in 250 ml tetrahydrofuran at a mass fraction of 10 wt%, mixing with the above aramid 1314 polymer solution to obtain a mixed solution, adding 5 wt % of the mass of the mixed solution of pore former polypyrrolidone, and stirring to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The above-mentioned casting liquid is coated on a stainless steel belt through a coating equipment, first passed through a steam bath with a temperature of 45°C and a humidity of 75%, then immersed in a water tank for phase inversion film formation, and then placed in a drying oven for drying and cooling to obtain the aramid lithium battery separator with low closed pores and high rupture properties, which is then rolled up to obtain the aramid lithium battery separator with low closed pores and high rupture properties.
9. A low closed-cell and high-breakdown aramid lithium battery separator, characterized in that: The aramid lithium battery separator with low closed pores and high membrane rupture is prepared by the following steps: Preparation of aramid 1314 polymer solution: Add CaCl2 to 250 ml of N-methylpyrrolidone under nitrogen protection, dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine in a mass ratio of 9:1, react in an ice water bath, slowly add 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride in a mass ratio of 9:1 while stirring, react for 30 minutes, add 0.74 g of calcium hydroxide for neutralization, and obtain an aramid 1314 polymer with a concentration of 10 wt / %; Preparation of casting solution: dissolving nylon 6 / 66 / 1010 terpolymer, nylon 6 / 66 / 610 terpolymer and polyvinylidene fluoride-trifluoroethylene in a mass ratio of 1:1:1 in 250 ml of tetrahydrofuran at a mass fraction of 10 wt%, and mixing with the above-mentioned aramid 1314 polymer solution in a volume ratio of 1:1 to obtain a mixed solution, adding 5 wt% of the mass of the mixed solution as pore-forming agents calcium chloride and lithium chloride, the mass ratio of the calcium chloride and lithium chloride being 1:1, and stirring evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The casting liquid is coated on a stainless steel belt through a coating device, firstly passed through a steam bath, the temperature of the steam bath is 45°C, the humidity is 75%, then immersed in a water tank for phase inversion film formation, then placed in a drying oven for drying and cooling to obtain the low closed-pore and high rupture aramid lithium battery separator, and then rolled up to obtain the low closed-pore and high rupture aramid lithium battery separator; The thickness of the low-closed-pore and high-breakage-film aramid lithium battery separator is 15 μm, the thermal closed-pore temperature is 112° C., the breakage temperature is 275° C., and the battery capacity retention rate of the low-closed-pore and high-breakage-film aramid lithium battery separator after 100 cycles is 97.5%.
10. A method for preparing the aramid lithium battery separator with low closed pores and high rupture rate according to claim 9, characterized in that: The following steps are involved: Preparation of aramid 1314 polymer solution: Add CaCl2 to 250 ml of N-methylpyrrolidone under nitrogen protection, dissolve 10.814 g of a mixture of p-phenylenediamine and m-phenylenediamine in a mass ratio of 9:1, react in an ice water bath, slowly add 20.302 g of a mixture of terephthaloyl chloride and isophthaloyl chloride in a mass ratio of 9:1 while stirring, react for 30 minutes, add 0.74 g of calcium hydroxide for neutralization, and obtain an aramid 1314 polymer with a concentration of 10 wt / %; Preparation of casting solution: dissolving nylon 6 / 66 / 1010 terpolymer, nylon 6 / 66 / 610 terpolymer and polyvinylidene fluoride-trifluoroethylene in a mass ratio of 1:1:1 in 250 ml of tetrahydrofuran at a mass fraction of 10 wt%, mixing with the above-mentioned aramid 1314 polymer solution to obtain a mixed solution, adding 5 wt% of the mass of the mixed solution as pore-forming agents calcium chloride and lithium chloride, the mass ratio of the calcium chloride and lithium chloride being 1:1, and stirring evenly to obtain a casting solution; Preparation of heat-resistant polymer porous layer: The above-mentioned casting liquid is coated on a stainless steel belt through a coating equipment, first passed through a steam bath with a temperature of 45°C and a humidity of 75%, then immersed in a water tank for phase inversion film formation, and then placed in a drying oven for drying and cooling to obtain the aramid lithium battery separator with low closed pores and high rupture properties, which is then rolled up to obtain the aramid lithium battery separator with low closed pores and high rupture properties.
Citation Information
Patent Citations
Preparation of polyvinylidene fluoride dewatering microporous film
CN101279211A
Lithium battery diaphragm and preparation method thereof
CN103378331A
Porous membrane, preparation method and lithium battery
CN109148790A